Negotiating the domain of mental capacity: Clinical judgement or judicial diagnosis?. (September 2016) - Case, Paula
'The decision on capacity is one for the judge to make'. 1 Deciding whose voices matter in the assessment of someone's decision-making capacity raises issues of social and legal policy. Despite legal judgments explicitly asserting that the law has the upper hand in mental capacity assessment, both statute and judgments from the Court of Protection (CoP) have to some extent endorsed capacity as largely the domain of medical expertise. Academics have claimed that the courts have historically adopted a 'deferential' or even 'medicalized' approach to expert evidence on this issue. Yet, it is vital that the CoP exercises rigorous scrutiny of capacity assessment, for while human rights discourse constructs 'objective medical expertise' as a safeguard against the arbitrary forfeiture of decision-making power, excessive deference can transform medical opinion from safeguard to a form of arbitrariness in its own right. This short sociolegal study combines quantitative and qualitative approaches to probe this suggestion of deference, drawing from a sample of over 60 CoP judgments where the issue of capacity was examined in some detail. In the course of undertaking this task, the article interrogates the notions of 'deference' and 'medicalization' to explore the intertwining of medical and legal domains on the issue of mental capacity.